FIGURATIVE LANGUAGE ANALYSIS “IN THE LONELY HOUR” ALBUM BY SAM SMITH - Hulu, Asmenlima (Universitas Nias Raya, 2024)
This research aimed to know the types of figurative language which are exist in the album